Process improvement in emergency units. Two analysis cases (2014)
This article shows a proposal to improve processes at two Emergency Units (One public and the other one Private) by applying Lean Manufacturing methodologies in Colombia. The Emergency Units in question offer long waiting times to assist patients, when compared to the standards established by The District Department of Health. Also, the Emergency Units fail to comply with the minimum required spaces stipulated in the Guide Manual for Emergency architectural design. A diagnosis of the situation is carried out to identify the activities that do not add value to the process. Subsequently, proposals are put forward regarding aspects such as improvement of processes, redesign of the emergency Units and the use of management indices to evaluate the fulfillment of objectives according to Lean Manufacturing applied to Hospitals. The applicability of the proposal to patients' waiting time is assessed using Arena-based simulations of the admitting-patient process proposed. Results show a waiting-time reduction of 61 and 62% in Triage 2, and 53 and 80% in Triage 3, respectively for each Emergency Unit.